TIMED UP AND GO PERFORMANCE IN OLDER PEOPLE WITH DIABETES MELLITUS: ASSOCIATIONS WITH SENSORIMOTOR FUNCTION, BALANCE, COGNITION, AND FALLS (International Journal of Physiotherapy, 2020)
Background: The Timed up and Go Test (TUG) is often used as a mobility measure in older people. However, it isunclear whether the TUG is useful for identifying fall risk in people with diabetes mellitus (DM) and which physical and cognitive/psychological factors influence the performance of this test.Objectives: To investigate whether slow TUG times (standard test and when performed with a secondary cognitive task (c-TUG)) are a risk factor for falls in older people with DM and to determine the relative contributions of a range of sensorimotor, balance and cognitive/psychological factors to TUG performance in this population.Methods: Community-dwelling people (n=103, mean age 61.57, SD=6.3) underwent the TUG and c-TUG tests aswell as quantitative tests of vision, peripheral sensation, strength, reaction time, balance, cognition, and fear of falling. Participants were then followed up for falls for six months.Results: Negative binomial regression analyses revealed that each 1s increase in TUG and c-TUG times increased the risk of falling by 29% and 13%, respectively. Multiple regression analyses identified vibration sense (p